2011
DOI: 10.1128/aac.01228-10
|View full text |Cite
|
Sign up to set email alerts
|

Three Residues in HIV-1 Matrix Contribute to Protease Inhibitor Susceptibility and Replication Capacity

Abstract: Other than cleavage site mutations, there is little data on specific positions within Gag that impact on HIV protease inhibitor susceptibility. We have recently shown that non-cleavage site mutations in gag, particularly within matrix protein can restore replication capacity and further reduce protease inhibitor drug susceptibility when coexpressed with a drug-resistant (mutant) protease. The matrix protein of this patient-derived virus was studied in order to identify specific changes responsible for this phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 32 publications
1
47
0
Order By: Relevance
“…The remaining four positively selected sites (positions 15, 54, 69, and 339) have not previously been associated with PI exposure nor predicted to be HLA/KIR. Two additional sites in Gag have been reported to be associated with PI failure, 17,28 including the HLA/KIR-selected position 79, but were not found to be positively selected in this analysis. In total, 21 of the 53 changes identified in the entire Gag gene following PI failure showed some evidence of selection pressure ( Fig.…”
Section: Figmentioning
confidence: 54%
“…The remaining four positively selected sites (positions 15, 54, 69, and 339) have not previously been associated with PI exposure nor predicted to be HLA/KIR. Two additional sites in Gag have been reported to be associated with PI failure, 17,28 including the HLA/KIR-selected position 79, but were not found to be positively selected in this analysis. In total, 21 of the 53 changes identified in the entire Gag gene following PI failure showed some evidence of selection pressure ( Fig.…”
Section: Figmentioning
confidence: 54%
“…The results presented here advance recent work in the field, using Potts models to study HIV-1 evolution (Barton et al 2016b;Butler et al 2016), by providing systematic prospective predictions quantifying the influence of specific multi-residue patterns on the tolerance of drug resistance mutations. Recent publications have reported that mutations near or distal to Gag cleavage sites play a role in promoting cleavage by drug-resistant and enzymatically deficient proteases, by selecting for mutations that increase substrate contacts with the protease active site, altering the flexibility of the cleavage site vicinity, or by as of yet unknown mechanisms Kolli et al 2009;Breuer et al 2011;Parry et al 2011;Fun et al 2012;Flynn et al 2015). This suggests that viral coevolution of Gag with selective protease mutations may further stabilize multiple resistance mutations; thus, the analysis of protease mutation patterns can be extended to include amino acid substitutions within Gag and the Gag-Pol polyprotein.…”
Section: Discussionmentioning
confidence: 99%
“…The regions of Gag and protease that undergo compensatory mutations are strikingly similar to those exhibiting significant intermolecular PREs, thereby providing a plausible underlying structural basis behind these mutations. For example, conservative noncleavage site mutations in MA, specifically K30R, R76K, Y79F, and T81A, restore the fitness deficit arising from drug-resistant protease by improving replication capacity and generating a significant reduction in susceptibility to protease inhibitors in vivo (14,29). These residues along with two other drug-resistance mutations, E12K and L75R, reside in regions of MA that give large intermolecular PREs.…”
Section: Correlation Of Sites Of Encounter Complexes With Compensatormentioning
confidence: 99%
“…A comparison of regions involved in transient Gag-protease encounter complexes with residues associated with drug-resistance mutations (14)(15)(16)(17)28) in Gag and protease is provided in Figs. 2D and 3C, respectively (also see Table S2 for additional details).…”
Section: Correlation Of Sites Of Encounter Complexes With Compensatormentioning
confidence: 99%
See 1 more Smart Citation